MENGANALISA SISTEM SEDIAAN TRADISIONAL DENGAN SISTEM JUST IN TIME DAN THEORY OF CONSTRAINT: STUDI KASUS PADA CV BERKAT ASIA YANG MEMILIH MENGGUNAKAN SISTEM JUST IN TIME - Oktadyahtul Asbi, Suci; Abdullah, Rudi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
This study aims to determine and analyse the traditional inventory system or method with the just in time system and the theory of constraints in a cooperative partnership company, namely CV Berkat Asia. This type of research is descriptive qualitative research with a case study approach. This research analyses and describes the phenomenon of applying certain methods in calculating the cost of goods manufactured. Based on information from the data, it is known that in the process of managing raw materials CV Berkat Asia the cost of ordering and shipping raw materials reaches Rp 2,000,000 / month, storage costs Rp 1,000,000 / month, by using just in time, the ordering of raw materials is carried out more frequently, namely 5 orders per month with the number of working days for 1 year only 10 months, with 26 working days each month. As a manufacturing industry that is still in the process of development, it is necessary to apply various methods of calculating production costs to find which method is most suitable for the company's activities, therefore CV Berkat Asia chose to use the just in time method.